Аналіз споживання енергетичних ресурсів при виробленні молочної кислоти - Баранов, Володимир Іванович (My University, 2001)
У відповідності з методичними положеннями з нормування питомих витрат паливно-енергетичних ресурсів проведено аналіз спожиання енергетичних ресурсів при виробленні молочної кислоти. Наведено питомі витрати теплової та електричної енергії за напрямами споживання. The consumption analysis of energy resources in the process of lactic acid production was performed in accordance with methodology for the regulation of unit costs of fuel and energy resources. The unit costs of thermal and electrical energy by the ways of its consumption were presented.
Keywords: молочна кислота; нормування; енерговитрати; теплова і електрична енергія; аналіз; lactic acid; introduction of norms; energy requirement; thermal and electrical energy; analysis